Fruit quality parameters of sweet cherry cultivars produced under rain protected plastic foil and general orchard conditions - Vaszily, Barbara (Acta Agraria Debreceniensis, 2010)
Due to global climate warming, frequency of negative weather effects (rainfall amounts, distribution, sortness) are increasing. Rainfallamounts and frequency has also great effect of sweet cherry fruit quality around fruit ripening. Determination of optimal technologicalbasics (such as first class fruit quality and economic value) are an important task in dynamically growing sweet cherry production. This canbe solved with introduction of a new intensive training system. One of the solutions can be rain protecting foil which can reduce fruitcracking and fruit rot. Without this option sweet cherry can not be grown in many countries. In this study, fruit quality parameters werecompared from a 10 year old intensive (4 x 1m) sweet cherry orchard. The effect of rain protecting foil was tested in comparison with fruitsfrom not covered tree